Effects of Educational Games-based on Digital Device on Children with Learning Disability in Memory - Kumar, Ravindra; Suraksha, (THE PRIMARY TEACHER, 2019)
Educational games have become very popular not only with children but elders also. Each and every child plays games at some point and many play regularly. These games are ubiquitous in children’s leisure environment but the motivational and skill-enhancing potentialities of this technology are being exploited increasingly in education. Quality educational games, which are challenging, instructive and absorbing, can make learning enjoyable and effective. The study reviews the literature on educational games based on digital device used by Children with Learning Disability in Memory (CWLDM). The study investigated educational games as remedial teaching for children with special needs with reference to memory among Grade V students. The study adopted the pre-test-post-test control group design.